AL-âÄLAM DALAM ALQURAN: (Analisis tentang Ayat-ayat Penciptaan) - Hasyim, Muhammad Syarif (Institut Agama Islam Negeri (IAIN) Palu, 2012)
Abstract: One of the objects of the philosophy studies is the nature. The thought of the natureÂ runs continuallyÂ to the things beyond the nature (metaphysics) and eventually comes to a conclusion that the existence of the nature must be in process. The philosophers argued that all things created must be in process, namely the process of emanation. The implication of this argument is that the nature is qadÄ«m, because it was created by God since qidam and azÄlÄ«. This argument was opposed by the theologists (mutakallimÄ«n). They said that the nature was something new and its existence was from nothing. These two different theories are supported by the dalÄ«ls of the Qurâan. Their interpretations on the verses of the Qurâan gave the opportunity to result in different argument. The reason is that the use of the terms in the Qurâan, whichÂ refer to the meaning of creating, is various, moreover when Â Â Â referring to the proposition which rejects the existence of the Â synonims in the Qurâan. Therefore,Â eventhough the meaning of the term âkhalaqa, badaâa and fatara is âto createâ, each this single word has its own substancial meaning.Kata Kunci: Alquran, filsafat, penciptaan alam, khalaqa, badaâa, fatara